DEVELOPING STUDENT’S SCIENTIFIC LITERACY BY INCORPORATING LOCAL TERMS AND SOCIOCULTURAL PHENOMENA INTO SCIENCE TEACHING-LEARNING PROCESS - Rizky Purnawati (PROJECT (Professional Journal of English Education), 2024)
The lack of integration between science and culture, students' social-life and science experiences, as well as between students' sociocultural and science world, creates a "gap" between both aspects. When students fail to transition their school science situation and knowledge to real-life cultural experience or vice versa, they refuse to learn science deeper because science might threaten their sociocultural beliefs. As a further consequence, this condition will result in low scientific literacy. It is essential to increase students' scientific and cultural literacy because it helps young generation to marry science and culture effectively. Based on literature review done by the author, it shows that integrating local language and sociocultural phenomena into science classrooms can enhance students' motivation and interest in science and increase learning achievement. Connecting more students' social-cultural aspects, particularly language and life experience, can help to increase scientific literacy.